Resepsi Penonton Terkait Kesehatan Mental Anak dalam Film Bolehkah Sekali Saja Ku Menangis - Teresa Eskavi Sonda; Novita Ika Purnamasari (CV. ITTC INDONESIA, 2026)
Children's mental health issues remain a serious problem within families, especially those experiencing conflict and disharmony (broken homes). Parents' low awareness of the importance of children's mental health and strong negative stigma in society leave children vulnerable to psychological disorders. The film Bolehkah Sekali Saja Ku Menangis represents this reality through its depiction of physical and verbal abuse within the family, which has an impact on the mental condition of children. This study aims to analyze the audience's reception of the issue of children's mental health as portrayed in the film, particularly from the perspective of children who have experienced mental health disorders due to broken home situations. This study uses a qualitative approach with Stuart Hall's reception analysis method. Data were collected through in-depth interviews with five informants aged 18–30 years who had broken home backgrounds and experiences of mental health disorders. The analysis technique was carried out by applying the encoding–decoding model to classify the informants' meanings into three reception positions, namely the dominant-hegemonic position, the negotiated position, and the oppositional position. The results show that audience reception of children's mental health issues is diverse. Differences in meaning are influenced by family background, personal experience, education level, and the social and cultural conditions of the informants. These findings confirm that the audience plays an active role in interpreting media messages, so that the meaning received is not always in line with the message constructed by the filmmaker.